KEHILANGAN BIOMASSA GAMBUT AKIBAT KEBAKARAN HUTAN - Wiri, .; Astiani, Dwi; Fernando, Togar (JURNAL HUTAN LESTARI, 2017)
Peat land is a wetland / water-saturated area composed of organic soil material, namely the remains of plants and plant tissue decaying with a thickness of more than 50cm comprising organic materials, either with a thickness of more than 45cm or layered together with mineral soil with thickness of 80cm and have a thick layer of organic material is more than 50cm. Peat serves as a repository of highest carbon reserve after a very large tree. Additionally peat has a role in the ecosystem of peatlands both in terms of hydrology, conservation of wildlife and vegetation. Kuala Dua Village in Kubu Raya has a fairly extensive peatlands with a depth of 1-4 meters. Fire is a phenomenon that often occurs in Kuala Dua Village including peat fires. The fires emit carbon that contribute to the increase of greenhouse gases (GHGs) into the atmosphere. So there is a need to do research on "Measuring the Loss of peat Biomass in the area of peat fires in Kuala Dua Village, Kubu Raya Regency". This study aims to measure the content of peat biomass lost due to forest fire in the village of Kuala Dua Raya campus. The method used was a survey method, and to determine the location of the observations was done intentionally (purposive sampling) with the measurement plot. In total there were 10 sampling plots with a size of 5m2 / plot and has 25 subplots / plots with a size of 1m2. Identification of the amount of peat biomass loss was done by measuring the distance from the peat surface of the sampling plot based on the volume of burnt peat method by Agus, et al (2011). The total volume of peat burnt in research plots was calculated in the amount of 39.14 kg / m3 with changes the depth of peat soil surface. The decrease was an average reduction of around 0.621m peat surface. The amount of peat biomass loss due to forest fires during research in the peat area of Kuala Dua Village amounted to 3379.47 kg / m3.Keywords : Carbon Emissions, Forest Fires, Peat Biomass and Kuala Dua Village